Economic Evaluation of the Portuguese Needle Exchange Program in Community Pharmacies (NEP-CP) - M Gouveia; AV Carneiro; S Costa; J Guerreiro; M Cary; G Jesus; M Gouveia; M Borges (Revista Portuguesa de Farmacoterapia, 2019)
Objectives To conduct a cost-effectiveness analysis comparing two scenarios of the Needle Exchange Program (NEP) in Portugal: with and without community pharmacies (CP).